Elementy cybernetycznego układu gospodarki narodowej - Sowińska, Leokadia (Wydział Prawa i Administracji UAM, 1973)
The general theory of regulation distinguishes two components of cybernetic systems, i. e. regulator acrid regulated system. The author is of opinion however, that it is neccessary to distinguish three further components. They are: 1) information channel with flowing information into that channel, 2) component called strategist and 3) indirect link. Without forejudging about the possibility and neccessity of distinction of all those components1 in cybernetic system in general, the author thinks, that it is neccessary to distinguish them in social-economic systems. The most complete considerations of that problem correspond to the economy, where the basic economic decisions concerning the whole economy are made at the central level. In such a type of economy the regulation can be successfully carried out by method of equalization of deviations.
The Components of Cybernetic System of the National Economy